The last spell - White, J. A. (White, J. A. Thickety., 2019)
Kara and Taff find themselves in a race against time to locate the missing pieces of the powerful Vulkera before the Spider Queen beats them to it. And the final-face off might be Kara's last chance to save those she loves the most.